Design of Carbon/Metal Oxide Hybrids for Electrochemical Energy Storage. Issue 47 (8th June 2018) - Fleischmann, Simon; Tolosa, Aura; Presser, Volker
Abstract: Next generation electrochemical energy storage materials that enable a combination of high specific energy, specific power, and cycling stability can be obtained by a hybridization approach. This involves electrode materials that contain carbon and metal oxide phases linked on a nanoscopic level and combine characteristics of supercapacitors and batteries. The combination of the components requires careful design to create synergistic effects for an increased electrochemical performance. Improved understanding of the role of carbon as a substrate has advanced the power handling and cycling stability of hybrid materials significantly in recent years. This Concept outlines different design strategies for the design of hybrid electrode materials: (1) the deposition of metal oxides on readily existing carbon substrates and (2) co‐synthesizing both carbon and metal oxide phase during the synthesis procedure. The implications of carbon properties on the hybrid material's structure and performance will be assessed and the impact of the hybrid electrode architecture will be analyzed. The advantages and disadvantages of all approaches are highlighted and strategies to overcome the latter will be proposed. Abstract : Carbon for storing energy : Electrochemical energy storage materials that combine a high specific energy, power, and cycling stability can be obtained by hybridizing carbon with metal oxides. The combination of the components on a nanoscopic scale requires careful design. Here, we discuss different synthesis strategies to achieve synergistic effects for an increased electrochemical performance. The focus of this Concept article is on the role of the carbon component of the hybrid material.